Jacqueline Klausner: capstone - Klausner, Jacqueline, artist (Colorado State University. Libraries, 2017)
The artist's statement: Life has vividness. It is full of wonder and a richness that far surpasses mere existence. As an artist with a creative eye, I wonder at the richness of symbolism in the world. I create art simply because I love to, and I aspire to integrate art and life. I have very playful ideas, and I like to inspire wonder by creating intriguing work. I have an attention to form and symbolism, thus I am able to draw complex and witty connections. I wish to capture the essence of the creative act by taking the basic forms of subjects and analyzing them to find symbolic purposes, using their form to convey an idea. Artistic expression is a way for me to analyze and interpret the world. Before approaching work, I sketch. My knack for writing influences my artistic process in sketching. When I write, one thing leads to another and I can't seem to stop. My thoughts and questions take control. In High School, I would sketch a couple of things, but it was in college that I realized the power of sketching because I was able to combine my love of writing into my artistic process. I write along with making thumbnails. Writing and sketching inspire one another. My sketches take the form of maps, charting the rampant and energetic thoughts that roam my mind. I use any material I believe will suit the need of realizing an idea. I use vector, paint, collage, patterned paper, photography, construction paper, ink and paper, and video. Programs I utilize are Illustrator, Photoshop, and Indesign. I have also been introduced to Adobe Premiere and After Effects. I simply love looking at the world around me, seeing the riddles that unfold. There is so much to discover, and I always aim to have my creative process involve the adventure of discovery, discovering meaning within the everyday. I question reality to try to see the possibilities, striving for different meanings and playing with irony. I love working with people, and I try to understand each person's depth and uniqueness, so that I may cater to their specific needs. People fascinate me and learning more about them enables me to serve them more fully.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design